How to Prepare Now for What's Next : a Guide to Thriving in an Age of Disruption. - McQueen, Michael (John Wiley & Sons, Incorporated, 2018)
Disruption is changing the playing field - keep your successful business on top Thriving businesses on top of their game are targets for disruption. But for savvy business owners and managers who understand the coming changes, the time to future-proof their successful companies is now. Following over a decade of research into future trends, business reinvention and disruptive innovation, author Michael McQueen presents How to Prepare Now for What's Next, a blueprint for top companies to thrive in turbulent times. McQueen brings rare insight to the topic of business disruption. The book first explores the notion of disruption itself, and confirms that the term is much more than just guru-speak. The book outlines the four primary forms of disruption that McQueen sees playing out over the next 5-10 years, and quickly moves on to the in-depth tools, tips and techniques that healthy businesses will need to stay on top.-Use a simple tool to assess just how vulnerable to disruption your company is -Read case studies, research and trend reports that highlight real-world examples to complement the book's concepts -Understand the four forms of disruption, namely widescale automation, empowered consumers, unconventional competition and emerging generations -Apply the 9 keys to future-proof your business against disruption and make it impervious to change The time to act is now for the businesses who want to keep their edge, and How to Prepare Now for What's Next is the guide to continue thriving.